Capital structure, company size, and Company value: test significance Moderate model - Akhmadi Akhmadi; Wawan Ichwanudin; Uyun Uyun (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This research at investigate wether the capital structure to the firm value by firm size as moderating variable in the LQ 45 Company listed in Indonesia Stock Exchanged period 2013-2017. In this research, firm value is measured by price to book value, capital structure is measured by debt to equity ratio, and firm size is measured by the natural logarithm of total assets. The population used 73 companies in this research is the entire of LQ 45 companies listed in Indonesia Stock Exchanged period 2013-2017. The research sample amounted to 30 companies and sampling used purposive sampling. The data analysis tool used in this research is moderated regression analysis (MRA). The result of this research showed that : capital structure (DER) is positive significant impact on the firm value, but firm size can't effect as moderating variabel.